The Ruins of the Abandoned Center of Gioiosa Guardia (Me). Studies and Investigations for a Memory to be Recovered - Carmen Genovese; Giovanni Minutoli (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
The abandoned city of Gioiosa Guardia, although in a state of ruin, still retains characters of considerable interest from various points of view: historical, architectural and naturalistic.